Chiral liquid membrane for enantioselective separation of racemic ibuprofen by l-tartaric acid derivatives1. Issue 52 (10th June 2015) - Zhang, Fan; He, Lichao; Sun, Wei; Cheng, Yongqi; Liu, Junteng; Ren, Zhongqi
<x xml:space="preserve">Abstract</x> Use of a chiral liquid membrane is an attractive separation method for racemic ibuprofen, and the separation factor could be up to 1.38 under optimal experimental conditions.